Genome-Wide Association Studies of 11 Agronomic Traits in Cassava (Manihot esculenta Crantz) - Zhang, Shengkui; Chen, Xin; Lu, Cheng; Ye, Jianqiu; Zou, Meiling; Lu, Kundian; Feng, Subin; Pei, Jinli; Liu, Chen; Zhou, Xincheng; Ma, Ping’an; Li, Zhaogui; et al. (Frontiers in Plant Science, 2018)
Cassava (Manihot esculenta Crantz) is a major tuberous crop produced worldwide. In this study, we sequenced 158 diverse cassava varieties and identified 349,827 single-nucleotide polymorphisms (SNPs) and indels. In each chromosome, the number of SNPs and the physical length of the respective chromosome were in agreement. Population structure analysis indicated that this panel can be divided into three subgroups. Genetic diversity analysis indicated that the average nucleotide diversity of the panel was 1.21×10−4 for all sampled landraces. This average nucleotide diversity was 1.97×10−4, 1.01×10−4, and 1.89×10−4 for subgroups 1, 2, and 3, respectively. Genome-wide linkage disequilibrium (LD) analysis demonstrated that the average LD was about 8 kb. We evaluated 158 cassava varieties under 11 different environments. Finally, we identified 36 loci that were related to 11 agronomic traits by genome-wide association analyses. Four loci were associated with two traits, and 62 candidate genes were identified in the peak SNP sites. We found that 40 of these genes showed different expression profiles in different tissues. Of the candidate genes related to storage roots, Manes.13G023300, Manes.16G000800, Manes.02G154700, Manes.02G192500 and Manes.09G099100 had higher expression levels in storage roots than in leaf and stem; on the other hand, of the candidate genes related to leaves, Manes.05G164500, Manes.05G164600, Manes.04G057300, Manes.01G202000 and Manes.03G186500 had higher expression levels in leaves than in storage roots and stem. This study provides basis for research on genetics and the genetic improvement of cassava.